Science effectively informs policy processes in Colombia toward low-emission agriculture: Reflections on the process of incorporating EC-LEDS research results into national low-carbon policies in agriculture - Bohórquez Lozano, Viviana; Martínez Barón, Deissy; Khatri-Chhetri, Arun (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The translation of low-emission development policies into implementation on the ground requires research outputs that can be developed in collaboration with key stakeholders. This helps to understand stakeholders’ roles and policy processes as well as enhancing technical capacity that facilitates the uptake of scientific results. An improved GHG National Inventory by decreasing uncertainties in emission calculations and estimates of emission reduction potential from cacao plantations can help to achieve Colombia’s Nationally Determined Contribution (NDC) target. Scaling the use of low-emission development research outputs need institutionalization and capacity strengthening of key stakeholders at different levels. There is a need to better support decision-makers’ use of technical information for strategic emission reductions planning, policy development, and implementation to deliver significant mitigation outcomes in agriculture. The creation of an effective communication platform, including LED resources, can serve this purpose.